DAMPAK KEMAMPUAN PENYUSUNAN LAPORAN KEUANGAN TERHADAP AKUNTABILITAS KEUANGAN BUM DESA (The Impact Of Financial Reporting Capability On Financial Accountability Of Village-Owned Enterprises) - Tata Rini, Yeni; Cicik Wijayanti, Tri (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2025)
This research is motivated by the phenomenon of low financial reporting capability in Village-Owned Enterprises (BUM Desa) which has implications for their financial accountability, especially after the issuance of the Minister of Village Decree Number 136 of 2022 concerning Guidelines for Preparing BUM Desa Financial Reports which requires stricter accounting standards. This study aims to analyze the impact of financial reporting capability on BUM Desa's financial accountability and identify factors influencing it. The research method used a qualitative approach with data collection techniques through interviews, observations, documentation, and focus group discussions at BUM Desa Sekar Makmur, Sekarpuro Village, Pakis District, Malang Regency. The results show that the majority of BUM Desa management faces substantial challenges in preparing financial reports according to applicable accounting standards due to limited knowledge and skills in accounting. BUM Desa financial accountability cannot be optimally realized due to the inability to prepare systematic and transparent financial reports, thus hampering the supervisory function of the Badan Permusyawaratan Desa (BPD) and community participation in evaluating BUM Desa performance. This research concludes that financial reporting capability significantly impacts BUM Desa's financial accountability, necessitating human resource capacity enhancement, implementation of integrated accounting information systems, and strengthening of monitoring mechanisms to realize accountable and transparent BUM Desa financial management.